Systems Biology - Al-Rubeai, Mohamed; Fussenegger, Martin; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
A comprehensive guide to the revolutionary area of systems biology and its application in cell culture engineering, this volume presents an overall picture of the current topics central to structural and functional genomics, proteomics, metabolomics and bioinformatics, including such hot topics as RNAi, metabolic engineering and unfolded protein response. It includes reviews of the cellular response of environmental modulation such as low temperature and osmolarity, critical assessments of the applications of metabolomics and fluxomics approaches, examination of the utility of modulation of key genes and a presentation of a theory of chemical organisation which provides a new view of the system's structure. The clearly written chapters by experts in the field describe methods applicable to investigating the unique facets of cell culture. The book should be of interest to all those working in cell culture development and drug discovery in pharmaceutical and biotechnology companies as well as in academic institutions. It provides an invaluable resource for students and researchers in biotechnology, cell culture, genomics and bioinformatics.
Structural Genomics -- RNA Interference in Haematopoietic and Leukaemic Cells -- Genomics and Proteomics of Chinese Hamster Ovary (CHO) Cells -- The Unfolded Protein Response -- Engineering of Cell Proliferation Via Myc Modulation -- The Molecular Response(s) During Cellular Adaptation to, and Recovery from, Sub-Physiological Temperatures -- Molecular Response to Osmotic Shock -- Metabolomics -- Metabolic Flux Analysis of Mammalian Cells -- Metabolic Engineering -- Chemical Organisation Theory -- Prokaryotic Systems Biology.
Keywords: LIFE SCIENCES; PROTEOMICS; BIOINFORMATICS; CYTOLOGY; MICROBIAL GENETICS; LIFE SCIENCES; PROTEOMICS; BIOINFORMATICS; CELL BIOLOGY; MICROBIAL GENETICS AND GENOMICS